The pro-autophagic protein AMBRA1 coordinates cell cycle progression by regulating CCND (cyclin D) stability. Issue 12 (2nd December 2021) - Maiani, Emiliano; Milletti, Giacomo; Cecconi, Francesco
ABSTRACT: The scaffold protein AMBRA1 regulates the early steps of autophagosome formation and cell growth, and its deficiency is associated with neurodevelopmental defects and cancer. In a recent study, we show that AMBRA1 is a key factor in the upstream branch of the MYCN-MYC and CDK4-CDK6-dependent regulation of G1 /S phase transition. Indeed, in the developing neuroepithelium, in neural stem cells, and in cancer cells, we demonstrate that AMBRA1 regulates the expression of D-type cyclins by controlling both their proteasomal degradation and their MYCN-MYC-mediated transcription. Also, we show that this regulation axis maintains genome integrity during DNA replication, and we identify a possible line of treatment for tumors downregulating AMBRA1 and/or overexpressing CCND1 (cyclin D1), by demonstrating that AMBRA1-depleted cells carry an AMBRA1 -loss-specific lethal sensitivity to CHEK1 inhibition. Interestingly, we show that this aspect is specific for AMBRA1 loss, because ATG7 knockdown does not display the same response to CHEK1 inhibitors. Hence, our findings underscore that the AMBRA1-CCND1 pathway represents a novel crucial mechanism of cell cycle regulation, deeply interconnected with genomic stability in development and cancer.